Demographics and Development Policy - Bloom, David E.; Canning, David (2012)
By late 2011 there will be more than 7 billion people in the world, with 8 billion in 2025 and 9 billion before 2050. New technologies and institutions, and a lot of hard work have enabled us to avoid widespread Malthusian misery. Global income per capita has increased 150 percent since 1960, outpacing the growth of population. But we cannot be sure that incomes will continue to grow.